2009
DOI: 10.1007/s10735-009-9229-y
|View full text |Cite
|
Sign up to set email alerts
|

Expression of gap junctional protein connexin43 during 4-nitroquinoline-1-oxide-induced rat tongue carcinogenesis

Abstract: Oral carcinogenesis is a multistep process and requires accumulation and interplay of a series of molecular genetic events. Gap junctions are intercellular channels composed of connexin subunits that mediate cell-cell communication. The disfunctions of gap junctions are believed to be associated with cancer development. We therefore investigated the expression of connexin (Cx)43, one of the major connexins in oral epithelia, during 4-nitroquinoline-1-oxide-induced rat tongue carcinogenesis. By immunohistochemi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 30 publications
0
6
0
1
Order By: Relevance
“…Our previous study indicated that TAOS1 and EMS1 amplifications and downregulation of Cx43 might be involved in oral carcinogenesis (Xia et al 2007(Xia et al , 2009. Chemokines are involved in cellular interactions and tropism in situations frequently associated with inflammation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our previous study indicated that TAOS1 and EMS1 amplifications and downregulation of Cx43 might be involved in oral carcinogenesis (Xia et al 2007(Xia et al , 2009. Chemokines are involved in cellular interactions and tropism in situations frequently associated with inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…Leukoplakic oral epithelia provide a useful model for exploring the molecular mechanisms of oral carcinogenesis (Xia et al 2007(Xia et al , 2009. In this study, we set out to evaluate the differential gene expressions of chemokines and chemokine receptors by microarray in surgically resected OLK specimens with epithelial dysplasia and normal epithelia, and validate our microarray results by real-time RT-PCR.…”
Section: Introductionmentioning
confidence: 99%
“…It was recently suggested that post-transcriptional, translational and degradation regulations play a similarly important gene transcription role in the determination of protein concentrations (33). Despite reduced Cx43 protein levels, normal high mRNA levels were detected (24). Budunova et al (34) investigated the expression of Cxs 26, 43 and 31.1 in mouse hyperplastic skin, papilloma and SCC.…”
Section: Descriptive ------------------------------------------------mentioning
confidence: 99%
“…In addition to significantly different expression patterns between the studied tissue types, high membrane Cx43 expression in OSCC tissues was found to be associated with poor prognosis (23). Xia et al (24) previously reported reduced Cx43 protein concentration, despite normal mRNA levels, in an induced rat tongue carcinogenesis model. The present study aimed to confirm the expression of the described Cx subtypes at the mRNA level by conducting a reverse transcription quantitative polymerase chain reaction (RT-qPCR) analysis in 15 tissue sample pairs of OSCC and corresponding oral mucosa.…”
Section: Introductionmentioning
confidence: 96%
“…Recently, Frank et al (12) reported that human tongue squamous cell carcinoma cells were deficient in Cx43 expression. Our previous study showed that Cx43 expression decreased during 4-nitroquinoline-1-oxide–induced rat carcinogenesis (13). These results indicate that OSCC has aberrant GJIC.…”
Section: Introductionmentioning
confidence: 99%